Kidung: Myth of Welfare for Kuthuk People in Kudus Regency - Bahtiar, Hafid Zuhdan (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2014)
The study is to describe the art of kidung in Kuthuk village Blora regency. This study used qualitative method with Structural Functional theory approach. Data in the form of the song, especially the lyrics and other data were used for primary data sources in addition to interviewing and observation. Data were analyzed qualitatively with structural and functional theory and anthropological approach developed by Malinowski. The result shows that the people of the village embracing many beliefs, have an art tradition of Puputan ritual. In Javanese culture, this ritual is done at the time of released cloth wrapping the baby’s navel. Kidung, an expression of the people when request welfare to God, reflects the acculturation between Islamic and non-religious beliefs, which characterize the people of those two cities that exist around Kuthuk village.